HAK KETERBUKAAN INFORMASI PUBLIK BERDASARKAN UNDANG - UNDANG KETERBUKAAN INFORMASI PUBLIK - Sri Agustini (Ensiklopedia Sosial Review, 2022)
The fall of the new order government has opened hope for a more democratic state life and the government's openness to society has become one of the demands on the agenda of the reform struggle. In the current reform era, the right to open public information has been guaranteed in Law No. 14 of 2008 concerning Openness of Public Information. However, there are still obstacles in fulfilling the right to open public information. Public bodies have not fully implemented Law No. 14 of 2008 on Public Information Disclosure. The problems in this research are the forms of the right to open public information based on Law No. 14 of 2008 concerning the Openness of Public Information, the fulfillment of the right to open public information and the obstacles faced in the fulfillment of the right to open public information. The research method used is sociological juridical, namely research conducted by examining applicable legal rules and seeing their implementation in the field. This study aims to determine the forms of public information disclosure rights, fulfillment of public information disclosure rights. As well as trying to realize a transparent government by properly implementing Law No. 14 of 2008 on Public Information Disclosure.Keywords: Transparency, Public Information, UU KIP.